MANAGEMENT OF INTEGRATED MADRASAH DINIYAH CURRICULUM DEVELOPMENT AT SD KHAZANAH ILMU SIDOARJO - Mohamad Rojii; Istikomah Istikomah; Choirul Mahfud; Moh. Saifulloh; Muhammad Zuhair (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2020)
Madrasah Diniyah emerged as a place for religious education for people who wanted a portion of their children's religious education. If this Diniyah Madrasah can be run according to its function and managed with good management, then the Diniyah Madrasah can be one solution to the problems of Religious Education in Indonesia. This study aims to reveal how the management of Madrasah Diniyah curriculum development is integrated into primary education institutions. This research includes qualitative research; data collection is done by collecting documents, conducting interviews, and observing at the research site. This study's data were analyzed using analytical techniques, including reduction, presentation of data, and concluding. The results of this study stated that the management of the integrated Madrasah Diniyah curriculum at SD Khazanah Sciences was carried out with a process including planning, organizing, implementing, monitoring, and evaluating the founders as initiators of curriculum development ideas at the institution. After that, a curriculum development team was formed with specific tasks according to their respective responsibilities to start the curriculum development process based on philosophical, psychological, sociological, and juridical foundations.Keywords: Management Curriculum Development, Integrated Madrasah Diniyah, Basic Education Institutions. Abstrak Madrasah Diniyah muncul sebagai wadah pendidikan Agama bagi masyarakat yang menginginkan porsi pendidikan Agama yang lebih banyak bagi anak-anak mereka. Jika Madrasah Diniyah ini dapat dijalankan sesuai dengan fungsinya dan dikelola dengan manajemen yang baik, maka Madrasah Diniyah dapat menjadi salah satu solusi bagi permasalahan Pendidikan Agama di Indonesia. Penelitian ini bertujuan untuk mengungkap bagaimana bentuk manajemen pengembangan kurikulum Madrasah Diniyah yang terintegrasi pada lembaga pendidikan dasar. Penelitian ini termasuk jenis penelitian kualitatif, pengumpulan data dilakukan dengan cara mengumpulkan dokumen-dokumen, melakukan wawancara, dan juga melakukan observasi di tempat penelitian. Adapun data pada penelitian ini dianalisis dengan menggunakan teknik analisis yang meliputi reduksi, penyajian data, dan penarikan kesimpulan. Hasil penelitian ini menyatakan bahwa manajemen pengembangan kurikulum Madrasah Diniyah terintegrasi di SD Khazanah Ilmu dilaksanakan dengan proses meliputi perencanaan, pengorganisasian, pelaksanaan, pengawasan, dan evaluasi para pendiri sebagai inisiator ide pengembangan kurikulum di lembaga tersebut. Setelah itu, dibentuklah tim pengembang kurikulum dengan tugas-tugas khusus sesuai tanggung jawab masing-masing untuk memulai proses pengembangan kurikulum dengan berlandaskan pada landasan filosofis, psikologis, sosiologis, dan yuridis.Kata Kunci: Manajemen Pengembangan Kurikulum, Madrasah Diniyah Terintegrasi, Lembaga Pendidikan Dasar.